Pelatihan Olahan Lele Sebagai Alternatif Pemberian Makanan Tambahan (PMT) Sebagai Optimalisasi Gizi Penanganan Balita Stunting Bagi Kader Posyandu Anggrek Bulan 1 Tiyasan - Veronica Ima Pujiastuti; Dita Hanna Febriani (LPPM UNINUS, 2022)
Posyandu cadres in Padukuhan Tiyasan Condongcatur are part of increasing the success of stunting reduction in Sleman Regency. The cadre problems are limited knowledge about stunting and nutritious food sources for toddlers and the lack of cadre skills in processing locally-based foods. This service activity's implementation methods are education, training, and mentoring. There are two main stages in implementing the program, the first stage of stunting education and an explanation of nutritious food for toddlers. The second stage is cadre training to process catfish nuggets with a